(untitled) (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2020)
"Apartment 2J" tells the story of three sets of people who inhabit the same apartment over the years and how their lives are interconnected. This excerpt is the first of the story’s three parts and chronicles a mother’s struggles and grief after her two-year-old daughter is kidnapped in broad daylight. For additional context, listen to the author’s reflection on the piece below.